Efferocytic Defects in Early Atherosclerosis Are Driven by GATA2 Overexpression in Macrophages - Yin, Charles; Vrieze, Angela M.; Rosoga, Mara; Akingbasote, James; Pawlak, Emily N.; Jacob, Rajesh Abraham; Hu, Jonathan; Sharma, Neha; Dikeakos, Jimmy D.; Barra, Lillian; Nagpal, A. Dave; Heit, Bryan (Frontiers in Immunology, 2020)
The loss of efferocytosis—the phagocytic clearance of apoptotic cells—is an initiating event in atherosclerotic plaque formation. While the loss of macrophage efferocytosis is a prerequisite for advanced plaque formation, the transcriptional and cellular events in the pre-lesion site that drive these defects are poorly defined. Transcriptomic analysis of macrophages recovered from early-stage human atherosclerotic lesions identified a 50-fold increase in the expression of GATA2, a transcription factor whose expression is normally restricted to the hematopoietic compartment. GATA2 overexpression in vitro recapitulated many of the functional defects reported in patient macrophages, including deficits at multiple stages in the efferocytic process. These findings included defects in the uptake of apoptotic cells, efferosome maturation, and in phagolysosome function. These efferocytic defects were a product of GATA2-driven alterations in the expression of key regulatory proteins, including Src-family kinases, Rab7 and components of both the vacuolar ATPase and NADPH oxidase complexes. In summary, these data identify a mechanism by which efferocytic capacity is lost in the early stages of plaque formation, thus setting the stage for the accumulation of uncleared apoptotic cells that comprise the bulk of atherosclerotic plaques.